(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Anti-mürellian hormone and Vitamin D in patients with proven breast cancer have been estimated to find the possibility of using such parameters as biomarkers in the diagnosis of breast cancer patients compared to control. Sera of (32) patients had been taken to estimate the levels of [AMH] & [VIT.D] at the period (March/2017-Julyl/2017). All studied patients samples were female with the range age (30-41) years. The present results showed a significant difference in statistic results at (P<0.05)fo AMH & VIT.D concentration of patients compared to healthy control. The results also showed a good correlation between [AMH] & [VIT.D] of patients which the value of correlation is (-0.91749) at level 0.05 and o.o1. The relation between A MH&VIT.D is inverse. There were( 9) patients detcelloc the samples before chemotherapy treatment and( 23) patients right samples when they treated with chemotherapy. According to t-test there was significant difference in both [AMH] & [VIT.D] between the previous groups at level (0.05). So this study recommended to use [AMH] & [VIT.D] in early detecting of the breast cancer disease in women at fertile age .